Axillary artery access for stenting of aortic coarctation in a 1.2 kg premature newborn with malignant systemic hypertension: a case report. Issue 2 (24th December 2020) - Esmaeili, Anoosh; Schrewe, Roland; Wong, Flora; Schranz, Dietmar
Abstract: Background : Axillary artery access is rarely used for demanding percutaneous transcatheter interventions. However, there are many clear advantages. Case summary : We describe this attractive approach in a 3-week-old premature neonate (bodyweight of 1.2 kg) with severe aortic coarctation. Percutaneous transcatheter intervention was performed with analgo-sedation and local anaesthesia; and a coronary stent was placed with a low fluoroscopy time of 2 min. Malignant systemic hypertension (160/54 mmHg) was effectively treated without any residual blood pressure gradient, with the aim for definitive surgery with stent resection and end-to-end anastomosis at the age of 6–12 months. Discussion : Axillary artery access is an attractive, alternative approach to treat newborns and premature infants with low body weight with complex heart diseases.